Exploring the Impact of Language Learning Platforms on Motivation to Learn English Among Moroccan ISTA Students - Brahim Mrissa (Yayasan Visi Intan Permata, 2025)
The increasing integration of digital learning platforms in education has raised questions about their impact on student motivation. This study explores the role of online platforms particularly Altissia, platfom for English language learning, in enhancing students' motivation to learn English. Through a quantitative approach, the study employs a questionnaire distributed to 200 participants to gauge the effectiveness of Altissia in fostering both intrinsic and extrinsic motivation. The research examines differences in motivation between male and female students, as well as the influence of students’ majors at ISTA. Findings suggest that while online learning platforms provide flexibility and accessibility, they may not always lead to increased engagement. Participants reported insufficient motivation when using Altissia, factors such as lack of interactivity, limited feedback, and a monotonous interface. These results align with some existing studies while contradicting others emphasizing the need for more interactive and engaging features in Altissia to best attract learners to the process of learning.